Design of a Soft-Switched 6-kW Battery Charger for Traction Applications - McGrath, B.P.; Holmes, D.G.; McGoldrick, P.J.; McIver, A.D. (IEEE transactions on power electronics, 2007)
Auxiliary power converters for traction rolling stock applications have to operate under difficult conditions, including high-input voltages which are subject to wide fluctuations, high temperatures, and harsh environmental constraints. Additionally there is often a need for silent operation, which implies switching frequencies above 20 kHz. Increasingly, high-frequency DC-DC converters are being used for these applications, with their advantages of reduced size and weight. However, the requirement to accommodate high-input voltages and switch at high frequencies is challenging for a conventional hard-switched converter based on IGBTs, which makes soft-switching topologies an attractive alternative. This paper presents the design strategy for a zero-voltage switched (ZVS) 6-kW battery charger switching at 20 kHz using IGBTs. This paper illustrates how the design is a tradeoff between managing the hard-switch turn-on losses at light load, minimizing the duty cycle loss caused by soft-switching delays, and minimizing the effects of tail current-switching losses. These tradeoffs affect the selection of the ZVS capacitors, the determination of the series inductance value, the transformer turns ratio, and the selection of the IGBTs to be used. Design details, theoretical predictions, and experimental results are presented in this paper for the conversion system that was developed.